Adults who do not want to participate in learning: a cross-national European analysis of their perceived barriers. Issue 3 (4th May 2017) - Roosmaa, Eve-Liis; Saar, Ellu
Abstract: This article explores cross-national differences in the intensity of perceived barriers to adult learning in Europe focusing on the barriers recognised by those not participating and having no intention to do so. This relatively large subgroup has received scant scholarly attention, yet exploring their participation barriers is critical for policies aimed at encouraging learning activity. The authors propose a country typology of adult learning based on earlier typologies of welfare state regimes, varieties of capitalism and models of lifelong learning. Multilevel analysis of 19 European countries reveals individual and contextual effects on barriers to adult learning. The results indicate substantial country differences in all types of barriers perceived. In general, in the Nordic countries adults not participating and not intending to participate in learning are the least impeded. For this group of adults, institutional barriers are perceived most often in the Baltic countries, situational barriers occur most frequently in liberal and continental countries, whereas dispositional barriers are most frequent in all post-socialist countries as well as in Southern Europe. This confirms the significance of including structural and institutional factors in addition to individual characteristics in explaining barriers to adult learning.